Analysis of the Dependence of the Apparent Sound Reduction Index on Excitation Noise Parameters - Ervin Lumnitzer; Miriam Andrejiova; Anna Yehorova (Applied Sciences, 2020)
In acoustic practice, established methods of measuring the acoustic properties of partition structures are used. Recommended procedures and means can be found in technical standards, but practice suggests that measurement results may also depend on measurement conditions. These procedures leave the choice of noise type, frequency interval examined, and excitation interval on the measurer. The aim of this research is to determine which parameter has a significant effect on the results, and to quantify the extent of this effect. We examined the type of noise, the frequency band of the sound passing through the partition structure and the excitation interval of the diffusion field in the rooms (hereinafter referred to as “excitation interval”). During the research, we conducted a number of repeated, statistically significant measurements, which we first evaluated by classical methods used in acoustic practice. We subjected the obtained results to a thorough mathematical analysis. Evaluation of the results shows that some measurement conditions significantly affect the resulting values, especially in the low-frequency spectrum. One of the most important elements which has an effect on the results is the type of excitation noise, which, when assessed in the source room, excites the diffuse sound field, and its transmission through the considered partition structure is measured. The significance of the investigated frequency interval was also demonstrated.